O audiovisual educativo no Brasil : um estudo de caso sobre a produção dos conteúdos digitais para o PNLD 2014 - Divardin, Danielle de Carla (2016)
We are living in a special moment of changes in the processes of communication, acquisition and production of knowledge provided by technological advances in information technology and telecommunications. The new forms of perception and building of knowledge have a direct effect on education. Schools, both private and public, try to adapt to this new reality by introducing digital technologies into educational practices. However, the use of educational technologies is not just about using the computer or the Internet. Cinema, radio and television have been used as tools to support education for a long time. Our starting point is a historical contextualization of the use of audiovisual technologies in education in Brazil to understand how these resources were included in teaching and learning practices along the years. We note a number of problems that are repeated and that disclose the technocratic and instrumental conception of the State regarding these resources. The revision of the historiographic aspect provides the basis for the understanding of the current production of digital educational contents, discussed in more detail through the case study on the production of Digital Educational Objects (OEDs) for the National Textbook - PNLD 2014. The public notice of PNLD 2014, for the first time included the delivery of multimedia content incorporated into printed textbooks. At this stage, consultations were carried out with several professionals involved in the format of the notice as well as in the production of OEDs (publishing houses and audiovisual producers) and in the evaluation of the objects. Also, consultations were carried out with the Electronic System for Citizen Information Service (e-SIC) and the data available on the FNDE website. With this analysis, we intend to understand the relations established in the editorial and audiovisual production market to meet the demand of the State, to investigate the production process of the objects and to identify the reasons that led to the discontinuity of this initiative.